Gestão acadêmico-pedagógica dos cursos de pós-graduação Lato Sensu : o modelo PUCRS online de educação a distância - Rauber, Ana Paula Erhart (2022)
Distance Education (EAD) is a reality in the Brazilian educational context. In Brazil, a distance education modality is part of the formal education system. The A Pontifícia Universidade Católica do Rio Grande do Sul (PUCRS) and its pioneering EAD model in Higher Education innovate by combining education and the job market. To understand the organization of the study-pedagogical model of Lato Sensu teaching courses, they integrate the online qualitative study of Distance Education, with the challenges of taxes that outline management as the type of study of qualitative research. For which a model application was carried out, in addition to a role for course coordinators, to understand the elements of the model organization and management process, the application of the course coordinator in these courses. Data were analyzed using the Likert-type scale. From the analysis of the results, it was possible to observe a greater role of the course coordinators in the stages of the course development process, when compared to the development of the portfolio. Furthermore, it was possible to identify, in addition to the role of the coordinator, especially in management, that these coordinators believe in the academic quality of the distance learning model of PUCRS Online.